THE IMPACT OF NATURAL GAS DEMAND ON RENEWABLE ENERGY DEVELOPMENT: A PANEL INVESTIGATION OF SIX ASIAN COUNTRIES - Sudaryanto, Annisa R.A Larasati (Universitas Muhammadiyah Yogyakarta, 2019)
The aim of this study is to assess the causal relationship of natural gas demand on the development of renewable energy in East and Southeast Asia. Specifically, the study examine the growth of natural gas and renewable energy consumption in both regions , determine the correlation of both energies and then measure the significant magnitude of the macroeconomic indicators in order to determine the development of renewable energy. The focus on the study was one Asian countries including China, Japan, South Korea to represent East Asia and Malaysia, Indonesia and Thailand to represent Southeast Asia. These countries are selected since they have contribute to the largest consumption in natural gas among other Asian countries. Although each of these countries have large potential renewable energy resource, these research found there are similar potential resources among the countries in each region. The quantitative research approach was applied to suit the time series secondary data collection.Â Panel data model then applied to enable researcher to determine the significant of macroeconomic indicators towards the development of renewable energy in East and Southeast Asia. With total of 90 observations, the macroeconomic variables include: natural gas consumption, GDP per capita, economic growth, exchange rate and access to electricity from period 2000-2014. Based on regression analysis, the findings revealed there is a significant coefficient between natural gas consumption on renewable energy development. A high consumption of natural gas would drive up the share of renewable energy to total final energy consumed. It is because these energy sources are not competitors yet complementary. However, the coefficient magnitude in Southeast Asia is higher than in East Asia. Consequently, other macroeconomic indicators such as exchange rate, GDP and electricity consumption has different effect on each region. These indicators can help the policy makers to improve the renewable energy policy which currently being implemented in order to induce the pace of renewable energy development in Asia.